2019
DOI: 10.1097/mnm.0000000000001102
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic imaging patterns in posterior cortical atrophy and Lewy body dementia

Abstract: Purpose To study the imaging patterns of Posterior cortical atrophy (PCA) and Dementia with Lewy bodies (DLB) on fluoro-deoxyglucose positron emission tomography computed tomography ([18F]FDG PET/CT), identify areas of overlap and differences and to develop a prediction model to assist in diagnosis using univariate and multivariate analysis. Methods A retrospective analysis of 72 patients clinically suspected of having posterior dementia was done. All p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Fluorodeoxyglucose positron emission tomography (FDG-PET) can demonstrate patterns of hypometabolism sensitive in differentiating AD from DLB, namely a temporoparietal distribution of hypometabolism in the former versus a more occipital distribution in the latter 9. However, such methods of differentiation have not been validated in PCA-AD which demonstrates overlap in metabolic imaging findings with DLB due to the more posterior location of hypometabolism 10. While quantitative imaging analysis techniques may prove useful in overcoming such pitfalls,10 further research is required to clarify the utility of imaging in differentiating PCA-AD from PCA-Plus which, given the unifying clinical findings, may demonstrate similar patterns of cortical atrophy and therefore be less sensitive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorodeoxyglucose positron emission tomography (FDG-PET) can demonstrate patterns of hypometabolism sensitive in differentiating AD from DLB, namely a temporoparietal distribution of hypometabolism in the former versus a more occipital distribution in the latter 9. However, such methods of differentiation have not been validated in PCA-AD which demonstrates overlap in metabolic imaging findings with DLB due to the more posterior location of hypometabolism 10. While quantitative imaging analysis techniques may prove useful in overcoming such pitfalls,10 further research is required to clarify the utility of imaging in differentiating PCA-AD from PCA-Plus which, given the unifying clinical findings, may demonstrate similar patterns of cortical atrophy and therefore be less sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…9 However, such methods of differentiation have not been validated in PCA-AD which demonstrates overlap in metabolic imaging findings with DLB due to the more posterior location of hypometabolism. 10 While quantitative imaging analysis techniques may prove useful in overcoming such pitfalls, 10 further research is required to clarify the utility of imaging in differentiating PCA-AD from PCA-Plus which, given the unifying clinical findings, may demonstrate similar patterns of cortical atrophy and therefore be less sensitive. CSF biomarkers have become an increasingly valuable element of the PCA work-up and should always be considered if available.…”
Section: Investigationsmentioning
confidence: 99%
“…DLB is associated with metabolic impairment in primary visual cortex which usually is spared in PCA, while the posterior cingulate gyrus is relatively preserved in PCA (“cingulate island sign”) [ 86 ]. However, some studies found a considerable overlap of patterns [ 87 ] or better discriminatory power for PCA with metabolic reduction in lateral temporal than in posterior cingulate cortex [ 88 ].…”
Section: Imaging Techniquesmentioning
confidence: 99%
“…Molecular imaging modalities, such as single-photon emission tomography (SPECT) and fluorine-18fluorodeoxyglucose positron emission imaging (FDG-PET), have played a pivotal role in understanding the complex pathophysiology of DLB by assessing metabolic activity in vivo with the correct radiotracers involved [14]. In DLB, metabolic studies show hypometabolism involving the occipital cortex, visual association areas, and posterior parietotemporal region [15]. However, in a comparative study, no significant differences were observed between PDD and DLB in terms of FDG uptake while PD patients without dementia exhibited similar profiles of metabolism as healthy controls [16].…”
Section: Metabolic Studiesmentioning
confidence: 99%